2016
DOI: 10.1073/pnas.1613623113
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four–nucleotide siRNAs produce heritable trans-chromosomal methylation in F1 Arabidopsis hybrids

Abstract: Hybrid Arabidopsis plants undergo epigenetic reprogramming producing decreased levels of 24-nt siRNAs and altered patterns of DNA methylation that can affect gene expression. Driving the changes in methylation are the processes trans-chromosomal methylation (TCM) and trans-chromosomal demethylation (TCdM). In TCM/TCdM the methylation state of one allele is altered to resemble the other allele. We show that Pol IV-dependent sRNAs are required to establish TCM events. The changes in DNA methylation and the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…These hypotheses are not mutually exclusive because both RdDM and meiotic silencing of unpaired DNA are dependent on an RNA-dependent RNA polymerase [ 27 , 25 ]. The involvement of RdDM is supported by several lines of evidence that link small RNAs and in particular 24-nt sRNAs with paramutation-like events in tomato in addition to the findings from other species [ 11 , 5 , 12 , 13 ]. At H06 , for example, the timing of the paramutation-like process correlates with the timing or sRNA production (Fig.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…These hypotheses are not mutually exclusive because both RdDM and meiotic silencing of unpaired DNA are dependent on an RNA-dependent RNA polymerase [ 27 , 25 ]. The involvement of RdDM is supported by several lines of evidence that link small RNAs and in particular 24-nt sRNAs with paramutation-like events in tomato in addition to the findings from other species [ 11 , 5 , 12 , 13 ]. At H06 , for example, the timing of the paramutation-like process correlates with the timing or sRNA production (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Genetic screens have implicated NRPD1 ( rmr6 [ 6 ]), the major subunit of Pol IV; the RNA-dependent RNA polymerase RDR2 ( mop1 [ 7 ]) and NRPD2a ( mop2 /rmr7 mutants [ 8 , 9 ]) the shared subunit of Pol IV and Pol V. These proteins are all required for RNA-directed DNA methylation (RdDM) in which DNA methytransferases are guided to the target sequence in the genome by base pairing of small RNAs (sRNAs). RdDM is also associated with paramutation of the SULFUREA locus in tomato [ 10 , 11 ] and trans-chromosomal DNA methylation in Arabidopsis thaliana hybrids [ 12 , 13 ]. Based on these findings the dominant model of paramutation implicates RdDM in the establishment and/or maintenance of the epigenetic mark.…”
Section: Introductionmentioning
confidence: 99%
“…2a). Over 99.5% of the reads (25,563) were uniquely mapped to the SRKIR Col-0 region; thus, we considered that these small RNAs were likely produced from this hairpin. The majority of these small RNAs had lengths of 20 or 21 nucleotides ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We named the sequence SRKIR C24 . Using the publicly available small RNA transcriptome dataset for the C24 strain 25 , we detected 3235 reads that mapped within the SRKIR C24 sequence in flower buds ( Supplementary Fig. 7b).…”
Section: Resultsmentioning
confidence: 99%
“…Greaves et al [ 55 ] suggested that DNA methylation sites in hybrids were frequently associated with regions that are differentially methylated in their inbred parents. In particular, methylated regions in the inbred parents were usually covered by the siRNA levels, and this implies that RNA-directed DNA methylation (RdDM) pathway may induce the remodeling of DNA methylation sites in hybrids to manifest heterosis [ 56 ].…”
Section: Molecular Bases Of Heterosismentioning
confidence: 99%